Collaborative Software for Supporting Communication and Cooperation in Project Teams - Muszyńska, Karolina (Oprogramowanie komunikacyjne wspomagające komunikację i współpracę w zespołach projektowych, 2010)
Communication and collaboration are processes which strongly influence the course and outcome of a project. Although not all aspects concerning these processes can be fully managed and structured, there are various tools whose appropriate appliance can aid effectiveness, transparency and efficiency of communication and collaboration processes. The aim of the paper is to specify and depict features and functionalities of different collaborative tools and software supporting communication and collaboration among project team members. This review aims at apprehending which features of available software and hardware can be utilized to develop a communication model in a project team, which could provide effective information and knowledge transfer among project team members and support communication process.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 205-217
Keywords: project communication; telecommunication tools; groupware; unified communications